Mobile Genetic Elements Associated with Third-Generation Cephalosporin Resistance in Klebsiella pneumoniae - Enggel, Yulia; Tjampakasari, Connny Riana; Kiranasari, Ariyani (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Klebsiella Â pneumoniae is the Enterobacteriaceae family can be found in the environment, humans and animals. These bacteria are common causes of hospital, community and healthcare associated infections. Third generation cephalosporin (3GC) is one of the broad spectrum cephalosporin antibiotic that is commonly used to treat this infection. Use of antibiotics without appropriate sensitivity guidance, natural antibiotic resistant bacteria and MGE mediated horizontal gene transfer have led to increased resistance in 3GC. Mobile genetic elements such as insertion sequences (IS), transposons, integrons and resistance plasmids facilitate horizontal gene transfer between bacteria. This element can move between chromosomes or plasmids, transferring genetic material to the recipient bacteria. Horizontal gene transfer can occur by conjugation, transformation, transduction and vesiduction. IS, transposons, integrons and resistance plasmids associated with 3GC resistance are discussed in this article. We analysed the role of these MGEs in 3GC resistance in K. pneumoniae using PRISMA methods from different academic sources. We found an association of MGE with ESBL and AmpC betalactamase gene. This element promotes the transfer of resistance genes to other bacteria. Understanding the MGEs that play a role in the spread of antibiotic resistance genes in K. pneumoniae is important to control the spread of the gene.